2012
DOI: 10.1111/j.1399-6576.2011.02627.x
|View full text |Cite
|
Sign up to set email alerts
|

Transillumination‐assisted orotracheal intubation: a comparison of the Bonfils fibrescope and the lightwand (Trachlight)

Abstract: For patients with normal airways, the Trachlight is superior for orotracheal intubation with respect to reliability, rapidity, and safety compared with the Bonfils fibrescope used with the transillumination technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…A number of studies reported a success rate of BIF intubation to be 82–100% [ 6 , 11 , 12 ]. In this study, the success rate of intubation with the transillumination-assisted technique was 97.3%, similar to that reported by Sui [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…A number of studies reported a success rate of BIF intubation to be 82–100% [ 6 , 11 , 12 ]. In this study, the success rate of intubation with the transillumination-assisted technique was 97.3%, similar to that reported by Sui [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Only one group reported the use of a retrograde transillumination technique , but they applied visible light, which does not specifically highlight the airway. Commercially available anterograde transillumination devices such as the Trachlight and Surch‐Lite stylets can be viewed as predecessors of IRRIS, but they have crucial limitations: they require suitably dimmed ambient light conditions (which are not always present); and are strongly dependent on the tissue thickness of the anterior neck region . To send visible light from the anterior surface of the neck in a reverse direction to the larynx, and to view it during direct laryngoscopy, seems to be at first glance a compelling alternative; however, this is technically not possible because visible wavelengths are not suitable to penetrate and selectively illuminate the airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, videolaryngoscopy has certain limitations, in particular, in the hands of less experienced users . Several adjuncts and manoeuvres are suggested to improve performance including using a flexible, rigid or malleable stylet within the tracheal tube to facilitate intubation , or using transillumination (such as with the Trachlight ™ , Saturn Biomedical System Burnaby, BC, Canada, or the Search‐Lite ™ , Bovie Medical Corporation, Clearwater, FL, USA) . One important limitation is that these latter methods require the device itself to intubate the trachea and the light is viewed emitted from within the lumen externally on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…
Sir,The recent article of J.-H. Sui et al 1 comparing the transillumination-assisted orotracheal intubation using the Bonfils fibrescope (Karl Storz, Tuttlingen, Germany) and the lightwand [Trachlight (Laerdal Medical Co., Wappingers Falls, NY, USA)] was of great interest. However, although they have provided valuable information, there are several aspects of this study that have to be clarified.
…”
mentioning
confidence: 99%
“…3,5,7 Furthermore, the brightness of its light source is poorer than that of Trachlight, as well reported by the authors. 1 Moreover, the longer intubation times with Bonfils fibrescope compared with Trachlight would be due to an improper use of the device; a first blind oral introduction was followed by an endoscopic view of the operator through the eyepiece to localise the glottis before tracheal tube's insertion. 7,8 We are conscious of the disadvantages of an endoscopic view due to secretions, blood or fogging, 7 but we think that it is the 'gold standard' for Bonfils fibrescope.…”
mentioning
confidence: 99%